Alexithymia as a Transdiagnostic Precursor to Empathy Abnormalities: The Functional Role of the Insula - Valdespino, Andrew; Antezana, Ligia; Ghane, Merage; Richey, John A. (Frontiers in Psychology, 2017)
Distorted empathic processing has been observed across multiple psychiatric disorders. Simulation theory provides a theoretical framework that proposes a mechanism through which empathy difficulties may arise. Specifically, introspection-centric simulation theory (IST) predicts that an inability to accurately interpret and describe internal affective states may lead to empathy difficulties. The purpose of this review is to synthesize and summarize an empirical literature suggesting that simulation theory provides insights into a cognitive and neurobiological mechanism (i.e., alexithymia and insula pathology) that negatively impacts empathic processing, in addition to how disruptions in these processes manifest across psychiatric disorders. Specifically, we review an emerging non-clinical literature suggesting that consistent with IST, alexithymia and associated insula pathology leads to empathy deficits. Subsequently, we highlight clinical research suggesting that a large number of disorders characterized by empathy pathology also feature alexithymia. Collectively, these findings motivate the importance for future work to establish the role of alexithymia in contributing to empathy deficits across clinical symptoms and disorders. The current review suggests that simulation theory provides a tractable conceptual platform for identifying a potential common cognitive and neural marker that is associated with empathy deficits across a wide array of diagnostic classes.